The Influence of Self-Service Technology on Customer Word-of-Mouth in Retail (International Journal of Scientific Research and Management (IJSRM), 2024)
In light of the vital role of word-of-mouth (WOM) in ensuring the success of retail establishments, this study investigates the influence of self-service technology (SST) on customer WOM within the Australian retail sector. Utilizing the theory of planned behavior (TPB) and the technological acceptance model (TAM), we analyze this relationship. Our research underscores the pivotal role of SST satisfaction as a mediator, clarifying how perceived control, ease of use, and usefulness impact WOM intention. Furthermore, employing structural equation modeling, we discern that perceived ease of use, usefulness, and perceived control exert differential effects on both SST satisfaction and WOM intention. These findings hold practical significance for store managers looking to leverage SST for the enhancement of customer recommendations and the fortification of retail success.